Presentation of the scientific program 'Sources for Croatian Heritage and Croatian European Identity' - Boras, Damir (2006)
History and identity of Croatian people can be viewed through written and material heritage accumulated over centuries onwards on one side and heritage that emerges at this moment on the other side. Projects gathered inside the program using multidisciplinary approach gether data of Croatian heritage, written and material, and tend to transform written heritage into machine readable form which will enable easier access to older Croatian written documents. The process will open up, still restricted, Croatian heritage for further research and start the process of creating database of material and written heritage locations as a basis of Croatian national identity. Existance of Croatian lexikography and encyclopedics in European science from 16th century witnesses continuation and acceptance of Croatian language and Croatia as a vital part of European identity. Croatias' integration in Europe can also be seen in numerous sources of Croatian historical documentation in various cultural institutions all around Europe. Bibliographical lexicon will list less known sources for researching Croatian national history outside Croatia and make them available for future research. // Researches of current and future involvement of Croatia in Europe tend to produce future Croatian heritage through lexicographical analysis of philosophical terminology and creation of encyclopedic film (cinematographic) terminology. Research will, in etnological database also list sources for research of ethnological movements in Croatia, and therefore also in Europe. // In a short term, program will undoubtedly strengthen the Croatian identity in regional and also but more in European surrounding. In the view of long term goals of Croatia's future development, program will, through its’ projects, realise the basic research induced by new knowledge acquisition in the field of cultural, biobibliographical, historical, ethnological, film art and lexicographical heritage. Program will develop new info-communication technology and methods in the field of humanities and social sciences and also Croatian identity. On the level of a single investigation, which will be undertaken within the framework of this program, embedded in scientific, cultural and political context, Croatia will be shown as equal to its European counterparts in the fields of lexicographic and graphic presentation of words throughout the history as well as today. On the other hand, Europe will investigate Croatian new age history as its integral part. Compiling the bibliography of Croatian heritage and creation of lists of ethnological and museum sources, the possibility to further the cultural tourism as a long term goal for Croatia. List will also serve as a base for locating heritage and become the initiator for not only Croatian but also European academic community. Creation of lexicons and dictionaries will strengthen cultural and linguistical identity of Croatia through phylosophical terms and encyclopedical approach to film art terminology. Cultural identity of Croatian people in Bosnia will be strengthened by research in Franciscian monasteries all around Bosnia.
Projekt MZOS
ENG